The Development of a Model Public Policy for a Smoke-Free University - กุจะพันธ์, จิรวุฒิ; Sungwalee, Wararat; Heebkaew Padchasuwan, Natnapa (Journal of Health Sciences and Wellness, 2020)
This study aimed to develop a model public policy for a smoke-free university. The study involved 274 students at a private university. The instrument used in the research was the development of a model public policy for a smoke-free university including a 4-step public policy model as follows: Step 1) exploring student smoking scenarios 2) planning to create a public policy 3) making a policy declaration for a non-smoking university 4) evaluating and collecting data using public policy awareness surveys, public policy, opinions and comments, questionnaires about perceived public policy and attitude of public policy towards a smoke-free university. Data were collected using questionnaires and analyzed by descriptive statistics, frequencies, percentages, averages, standard deviations and comparing means between before and after the policy development by using paired sample t-test at statistically significant levels of 0.05. The incidence of smoking among students is 15.33%. The public policy development process towards a non-smoking university used planning to create public policy. This process included appointing a public policy committee for a non-smoking and alcohol-free university, appointing young volunteers to establish a non-smoking university, setting a public policy, organizing a public policy forum for all students and staff to be aware and observe the precepts and setting up a non-smoking environment for designating non-smoking areas within the university. The mean scores between before and after the model started, about the perception and attitude towards a public policy for a smoke-free university ,increased by a statistically significant amount (p < 0.001). Therefore, the development of public policy for a smoke-free university is something that every institution should give attention to. It will help to stop new smokers and encourage smokers’ awareness towards reducing and quitting smoking.